Local translation and retrograde axonal transport of CREB regulates IL-6-induced nociceptive plasticity - Melemedjian, Ohannes K (BioMed Central, 2014)
Transcriptional regulation of genes by cyclic AMP response element binding protein (CREB) is essential for the maintenance of long-term memory. Moreover, retrograde axonal trafficking of CREB in response to nerve growth factor (NGF) is critical for the survival of developing primary sensory neurons. We have previously demonstrated that hindpaw injection of interleukin-6 (IL-6) induces mechanical hypersensitivity and hyperalgesic priming that is prevented by the local injection of protein synthesis inhibitors. However, proteins that are locally synthesized that might lead to this effect have not been identified. We hypothesized that retrograde axonal trafficking of nascently synthesized CREB might link local, activity-dependent translation to nociceptive plasticity. To test this hypothesis, we determined if IL-6 enhances the expression of CREB and if it subsequently undergoes retrograde axonal transport. IL-6 treatment of sensory neurons in vitro caused an increase in CREB protein and in vivo treatment evoked an increase in CREB in the sciatic nerve consistent with retrograde transport. Importantly, co-injection of IL-6 with the methionine analogue azido-homoalanine (AHA), to assess nascently synthesized proteins, revealed an increase in CREB containing AHA in the sciatic nerve 2 hrs post injection, indicating retrograde transport of nascently synthesized CREB. Behaviorally, blockade of retrograde transport by disruption of microtubules or inhibition of dynein or intrathecal injection of cAMP response element (CRE) consensus sequence DNA oligonucleotides, which act as decoys for CREB DNA binding, prevented the development of IL-6-induced mechanical hypersensitivity and hyperalgesic priming. Consistent with previous studies in inflammatory models, intraplantar IL-6 enhanced the expression of BDNF in dorsal root ganglion (DRG). This effect was blocked by inhibition of retrograde axonal transport and by intrathecal CRE oligonucleotides. Collectively, these findings point to a novel mechanism of axonal translation and retrograde trafficking linking locally-generated signals to long-term nociceptive sensitization.